STRATEGI PENDAYAGUNAAN ZAKAT PRODUKTIF UNTUK PEMBERDAYAAN KESEJAHTERAAN MUSTAHIQ - Dewi dewi (Jurnal Penelitian Agama, 2017)
Abstract : The Utilization Program of zakat, infak, and alms LAZISNU Banyumas there are four namely: Nu-Preneur, Nu-Smart, Nu-Skill, and Nu-Care. However, by 2017 following LAZISNU provisions, the Center will be replaced with education programs, economic programs, health programs and disaster programs. In maximizing the four programs, especially the Nu-Preneur (economic) program management strategy is using network approach, mustahik character, and business condition mustahik. The utilization of productive zakat in order to empower the mustahik welfare is valued effective. The effective use of zakat is considered effective in empowering the mustahik welfare and it can be measured from several elements, namely: The accuracy of program targets, program socialization, program objectives and program monitoring. Keywords: Program, utilization, LAZIZNU.